Alcohol consumption and alcohol problems after bariatric surgery in the swedish obese subjects study. (31st May 2013) - Svensson, Per‐Arne; Anveden, Åsa; Romeo, Stefano; Peltonen, Markku; Ahlin, Sofie; Burza, Maria Antonella; Carlsson, Björn; Jacobson, Peter; Lindroos, Anna‐Karin; Lönroth, Hans; Maglio, Cristina; Näslund, Ingmar; et al.
<x xml:space="preserve">Abstract</x> Objective Increased sensitivity to alcohol after gastric bypass has been described. The aim of this study was to investigate whether bariatric surgery is associated with alcohol problems. Design and Methods The prospective, controlled Swedish Obese Subjects (SOS) study enrolled 2, 010 obese patients who underwent bariatric surgery (68% vertical banded gastroplasty (VBG), 19% banding, and 13% gastric bypass) and 2, 037 matched controls. Patients were recruited between 1987 and 2001. Data on alcohol abuse diagnoses, self‐reported alcohol consumption, and alcohol problems were obtained from the National Patient Register and questionnaires. Follow‐up time was 8‐22 years. Results During follow‐up, 93.1% of the surgery patients and 96.0% of the controls reported alcohol consumption classified as low risk by the World Health Organization (WHO). However, compared to controls, the gastric bypass group had increased risk of alcohol abuse diagnoses (adjusted hazard ratio [adjHR] = 4.97), alcohol consumption at least at the WHO medium risk level (adjHR = 2.69), and alcohol problems (adjHR = 5.91). VBG increased the risk of these conditions with adjHRs of 2.23, 1.52, and 2.30, respectively, while banding was not different from controls. Conclusions Alcohol consumption, alcohol problems, and alcohol abuse are increased after gastric bypass and VBG.